Making New Zealand's pop renaissance : state, markets, musicians - Scott, Michael, 1971- (Ashgate popular and folk music series., 2013)
Michael Scott argues that New Zealand's pop music renaissance of the early 2000s was supported by state policies. He shows how the state built market opportunities for popular musicians through public-private partnerships and organisational affinity with existing music industry institutions. New Zealand offers an instructive case for the ways in which 'after neo-liberal' states steer and co-ordinate popular culture into market exchange by incentivising cultural production.